POLICY STRATEGY DIRECTIONS FOR MANGROVE ECOSYSTEM GOVERNANCE IN CLIMATE CHANGE MITIGATION EFFORTS AT MENIPO NATURE TOURISM PARK - Nopemnanu, Habel Martin; Dima, Alfred O.M; Marimpan, Lusia Sulo; Nufus, Mitha Rabiyatul; Kurniawan, Hendra; Marpaung, Sutan Sahala Muda (Jurnal Silva Samalas, 2026)
Mangrove ecosystem management plays an important role in achieving the Sustainable Development Goals (SDGs), particularly in protecting coastal and marine ecosystems from environmental degradation. Mangrove forests also contribute to climate change mitigation as blue carbon ecosystems through their capacity to absorb and store large amounts of carbon. This study aimed to analyze mangrove vegetation community structure, carbon potential, and management strategies for climate change mitigation in Menipo Nature Tourism Park (TWA Menipo), Indonesia. Data were collected using both qualitative and quantitative methods. The study identified 15 mangrove species, with Rhizophora mucronata, Bruguiera gymnorrhiza, Rhizophora stylosa, and Bruguiera parviflora as the dominant species. The vegetation exhibited a moderate diversity index, low evenness, and low species richness. Total biomass was estimated at 1,959.27 t/ha, while carbon stock and CO₂ sequestration potential reached 920.86 t/ha and 3,376.48 t/ha, respectively, highlighting the significant ecological role of mangroves as carbon sinks. The main driving factors influencing management direction were the sustainability of mangrove rehabilitation programs and the level of ecosystem degradation. Key stakeholders included Mangrove Farmer Groups, Non-Governmental Organizations (NGOs), the East Nusa Tenggara Natural Resources Conservation Agency (BKSDA NTT), village governments, and traditional leaders. Recommended management strategies include conducting biophysical assessments prior to rehabilitation, strengthening customary regulations, empowering local communities through social forestry programs, allowing sustainable harvesting of fishery resources without damaging mangrove habitats, providing designated boat-parking areas, and developing priority zoning maps for rehabilitation. These measures are expected to support sustainable mangrove conservation and enhance climate change mitigation efforts.